Rural Indigenousness : A History of Iroquoian and Algonquian Peoples of the Adirondacks - Otis, Melissa (Book collections on Project MUSE., 2018)
"This social history of Algonquian and Iroquoian peoples in the Adirondacks explores Indigenous and settler society contact in an Indigenous homeland where many exchanges occurred. While focusing on the long nineteenth century, the narrative extends before and after, providing a study of continuity and change in this space"--Provided by publisher